Internal friction in vanadium after heating at low air pressure - Mondino, Manuel Ángel; Vasallo, Daniel; De Achterberg, M. C. (Chapman and Hall, 1969)
Fil: Mondino, Manuel Ángel Comisión Nacional de Energía Atómica; Argentina